"We gon be alright:" containment, creativity, and the birth of hip-hop. (July 2021) - Shabazz, Rashad
In the United States, Black cultural production is bound up with geographic containment, restrictions on mobility, and racial segregation. Jazz, hip-hop, house music, and the Minneapolis Sound (the music associated with late recording artist, Prince) were mid-wifed by some of the most repressive systems of geographic order. Indeed, containment and creativity, geographies of trouble and hope are hallmarks of Black cultural production. This dialectic calls into question the belief that art can only be created in conducive or untroubled spaces. Hip-hop provides a perfect case study to challenge this assumption. Born in the Bronx, NY in the early 1970's, hip-hop was a cultural movement that emerged in against the backdrop of racial and economic segregation, mass incarceration, and joblessness. Yet, hop-hop "danced its way of these constrictions" and created geographies of hope. In doing this, hip-hop shows that Black cultural production and the radical imagination from which it springs, have the capacity to create counter-spatial imaginaries that challenge those under which it was produced. To that end, this article addresses the relationship between creativity and containment. Through linking the rise of carceral power, racially restrictive housing practices, a deindustrializing economy, and expanding prison populations with the hip-hop, I demonstrate the dialectic between systematic spatial containment of poor and working-class Black and Latinx Americans and the role it played in creation of the world's most powerful cultural force.